AtCERK1 Phosphorylation Site S493 Contributes to the Transphosphorylation of Downstream Components for Chitin-Induced Immune Signaling. (23rd May 2019) - Suzuki, Maruya; Yoshida, Issei; Suto, Kenkichi; Desaki, Yoshitake; Shibuya, Naoto; Kaku, Hanae
Abstract: While ligand-induced autophosphorylation of receptor-like kinases (RLKs) is known to be critical for triggering the downstream responses, biochemical mechanism by which each phosphorylation site contributes to the initiation of corresponding signaling cascades is only poorly understood, except the involvement of some phosphorylation sites in the regulation of catalytic activity of these RLKs. In this article, we first confirmed that the phosphorylation of S493 of AtCERK1 is involved in the regulation of chitin-induced defense responses by the complementation of an atcerk1 mutant with AtCERK1(S493A) cDNA. In vitro kinase assay with the heterologously expressed kinase domain of AtCERK1, GST-AtCERK1cyt, showed that the S493A mutation did not affect the autophosphorylation of AtCERK1 itself but diminished the transphosphorylation of downstream signaling components, PBL27 and PUB4. On the other hand, a phosphomimetic mutant, GST-AtCERK1(S493D)cyt, transphosphorylated these substrates as similar to the wild type AtCERK1. These results suggested that the phosphorylation of S493 does not contribute to the regulation of catalytic activity but plays an important role for the transphosphorylation of the downstream signaling components, thus contributing to the initiation of chitin signaling. To our knowledge, it is a novel finding that a specific phosphorylation site contributes to the regulation of transphosphorylation activity of RLKs. Further studies on the structural basis by which S493 phosphorylation contributes to the regulation of transphosphorylation would contribute to the understanding how the ligand-induced autophosphorylation of RLKs properly regulates the downstream signaling.